The Influence of Work Facilities on Employee Work Effectiveness at the Permata Keluarga Sribhawono Clinic, East Lampung - Hana Betel Kartina; Farida Yuliaty (Dinasti Publisher, 2025)
This study aims to determine the effect of work facilities on employee work effectiveness at the Permata Keluarga Sribhawono Clinic in East Lampung. In this study the authors used quantitative research methods, data collection techniques through surveys using questionnaires. The analysis technique used Smart PlS 3. The sample in this study amounted to 30 people. The results showed that work facilities affect the effectiveness of employee work at the Permata Keluarga Sribhawono Clinic in East Lampung, this can be seen from the Original Sample value of 0.817 (positive), the t-statistic value of 10.287> 1.96, the P-Value value of 0.000 <0.05.